1995
DOI: 10.1523/jneurosci.15-05-03863.1995
|View full text |Cite
|
Sign up to set email alerts
|

Forelimb akinesia in the rat Parkinson model: differential effects of dopamine agonists and nigral transplants as assessed by a new stepping test

Abstract: Methods for the assessment of akinesia in the unilateral rat Parkinson model have so far been lacking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
397
1
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 565 publications
(426 citation statements)
references
References 28 publications
26
397
1
2
Order By: Relevance
“…By lifting the animal's hindlimbs and one forelimb off the ground, each forelimb can be examined separately for impairments. In response to a rapidly imposed shift of weight on a smooth surface, parkinsonian rats often brace or drag the impaired forelimb instead of making adjusting steps, but step readily with the non-impaired forelimb to maintain center of gravity (Olsson et al, 1995;Schallert et al, 1979Schallert et al, , 1992. In this report we show that on a rough surface, which prevents the bracing reaction, moving the animal forward induces stepping with either the impaired or the unimpaired forelimb to regain center of gravity.…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…By lifting the animal's hindlimbs and one forelimb off the ground, each forelimb can be examined separately for impairments. In response to a rapidly imposed shift of weight on a smooth surface, parkinsonian rats often brace or drag the impaired forelimb instead of making adjusting steps, but step readily with the non-impaired forelimb to maintain center of gravity (Olsson et al, 1995;Schallert et al, 1979Schallert et al, , 1992. In this report we show that on a rough surface, which prevents the bracing reaction, moving the animal forward induces stepping with either the impaired or the unimpaired forelimb to regain center of gravity.…”
Section: Introductionmentioning
confidence: 65%
“…We performed three trials on each forelimb on a given day of testing. This is a new test that is a refinement of an earlier test variously referred to as the stepping test, adjusting-steps test, or bracing test (Schallert et al, 1979Olsson et al, 1995;Schallert and Tillerson, 2000;Woodlee et al, 2004) which, in contrast to the present test, measured number of steps taken across a set distance of displacement (in 6-OHDA rats these tests showed that the number of contralateral forelimb steps were reduced compared to the number of ipsilateral steps, due to bracing reactions on a smooth surface). Earlier pilot work with the PIT test in our lab and others (J. Mithyantha and P. A. Garris, unpublished data) also measured subsequent multiple steps (i.e., continuing to move the rat forward after the first catch-up step until an additional step or two had been made), as well as sideways stepping (measuring lateral displacement required in either direction to trigger a step), but found that these measures were not more sensitive or qualitatively different in dopamine depleted rats than the easier-to-perform version of the test described above.…”
Section: Postural Instability Test (Pit)mentioning
confidence: 99%
“…Dosage was balanced according to rotational behavior because contraversive turning is an index of severe nigrostriatal damage and postsynaptic supersensitivity (Ungerstedt, 1976), which in turn have been linked to dyskinesia (Nutt, 2000). Antiparkinsonian effects can be obtained with lower doses of dopamine agonists (Olsson et al, 1995) and there is no correlation between contraversive rotational behavior and improvement in motor disability (Lundblad et al, 2002;Metz and Whishaw, 2002). Therefore, the drug-induced changes in BOLD described here can be related to dyskinesia.…”
Section: Experimental Designmentioning
confidence: 78%
“…The post-operative diet of lesioned rats was supplemented with fruit and enriched jello to maintain weight. Five to seven days after surgery, rats were screened for lesion efficacy by step testing (Olsson et al, 1995). Only rats that demonstrated a strong lesion effect in behavior (number of steps by contralateral limb/ number of steps by ipsilateral limb < 10%) were used for electrophysiology.…”
Section: Experimental Procedures Nigrostriatal Lesions and Behavioralmentioning
confidence: 99%